'Communities are where it all happens': Tracing discourses of sustainability in the destatisation of adult literacy education in British Columbia, Canada - Suzanne Smythe (University of Bologna, 2014)
Using tools of critical discourse analysis and the concept of 'strategic ambiguity' (Eisenburg, 1984; Leitch & Davenport, 2007), the author traces the keyword 'sustainability' across the textual landscape of a literacy policy project in British Columbia, arguing that the ambiguity of the term sustainability allowed for consensus to coalesce around a policy project oriented to the destatisation (Jessop, 2002) of adult literacy education. The case suggests implications for how policy networks are "discourse-driven" and the importance for literacy educators and those in less powerful positions in a policy network to attend carefully to how words are used to gain consensus for controversial policy projects.